Problems Of Information And Psychological Security In Open Information Systems (Eurasian Journal of Humanities and Social Sciences, 2025)
The article explores the growing challenges of information and psychological security within open information systems in the digital era. It examines how rapid technological advancement and the expansion of global information flows influence human consciousness, social behavior, and state stability. The study highlights the dual nature of information — as both a constructive force for social progress and a potential source of psychological and moral threats.